1983
DOI: 10.1007/bf01310858
|View full text |Cite
|
Sign up to set email alerts
|

Replication of thymidine kinase deficient herpes simplex virus type 1 in neuronal cell culture: Infection of the PC 12 cell

Abstract: Replication of a thymidine kinase deficient (TK-) mutant of herpes simplex virus type 1 (HSV-1) was compared to replication of its parental TK+ strain in the PC 12 cell. This is a cell which ceases cell division and undergoes neuron-like morphological and physiological differentiation in the presence of nerve growth factor (NGF). No difference between mutant and parental strain replication was detected either when these cells were infected in the proliferative state or while maintained under the influence of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, unlike lentiviruses, these large dsDNA viruses encode dNTP biosynthesis proteins such as ribonucleotide reductase (RNR) and thymidine kinase (TK) that supply essential dNTP substrates for the viral DNA polymerase. Both of these genes are dispensable for HSV-1 viral replication in dividing cells, but are essential for replication under serum-starvation/non-dividing conditions where dNTP pools are limited [31], [32]. Thus, it is plausible that the dNTP biosynthesis machinery of dsDNA viruses promotes efficient replication in both dividing and non-dividing target cell types.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike lentiviruses, these large dsDNA viruses encode dNTP biosynthesis proteins such as ribonucleotide reductase (RNR) and thymidine kinase (TK) that supply essential dNTP substrates for the viral DNA polymerase. Both of these genes are dispensable for HSV-1 viral replication in dividing cells, but are essential for replication under serum-starvation/non-dividing conditions where dNTP pools are limited [31], [32]. Thus, it is plausible that the dNTP biosynthesis machinery of dsDNA viruses promotes efficient replication in both dividing and non-dividing target cell types.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were infected with HSV-1 strain KOS(M) (51) at a multiplicity of infection (MOI) of 1. Single-step growth curves confirmed that both differentiated and undifferentiated cells were permissive for HSV-1 infection (data not shown) (38). To examine the LAT gene transcripts expressed, total RNA was isolated from cells lysed in the presence of 5.5 M guanidinium isothiocyanate (Gibco-Bethesda Research Laboratories) by centrifugation through a cushion of cesium trifluoroacetate (Pharmacia-LKB).…”
mentioning
confidence: 86%
“…In this study, we have examined the stability and conformation of the 2-kb LAT gene transcript expressed in PC12 cells productively infected with HSV-1. PC12 cells differentiate into cells resembling sympathetic neurons after treatment with nerve growth factor (NGF) (21) and have been used by several investigators to study the interaction between HSV-1 and neuronal cells in culture (3,38,39). They support high levels of LAT promoter activity compared with other cell lines (5,29).…”
mentioning
confidence: 99%
“…However, in the rabbit model, Tk activity is not required for ganglionic infection [55]. Further studies using the mouse model demonstrate that only minimal Tk activity is sufficient for ganglionic infection [56] and that HSV-1 Tk -null virus can replicate in neuronal cells [57]. In addition, using PCR to increase the detection of virus DNA, low copies of HSV-1 Tk-null DNA were found in mouse TG following corneal infection [58].…”
Section: Seeding the Ganglion With Virusmentioning
confidence: 99%